2012
DOI: 10.18512/1980-6477/rbms.v11n3p278-290
|View full text |Cite
|
Sign up to set email alerts
|

Variedades de Sorgo Sacarino em Diferentes Espaçamentos e População de Plantas

Abstract: RESUMO-O sorgo sacarino surgiu como importante alternativa para a geração de biomassa na produção de etanol. Este trabalho objetivou avaliar o efeito do espaçamento entrelinhas e da população de plantas sobre a produção de sorgo sacarino em diferentes locais. Foram instalados dois experimentos, em duas localidades, Patos de Minas, MG e Sete Lagoas, MG, utilizando as cultivares BRS 505 e CMSXS 647, respectivamente. O delineamento experimental utilizado foi em blocos ao acaso, em esquema fatorial 4 x 4, sendo qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 14 publications
7
18
0
Order By: Relevance
“…Fiber (F) level varied from 14 to 15 % (Table 3), which was in agreement with previous studies using the cultivar BRS 506 (Santos, 2007;Borges et al, 2010;Durães et al, 2012;May et al, 2012). The highest mean value was observed for the March sowing because it had the lowest PC, S, and Q.…”
Section: Monitoring Of the Soil Water Content According To The Llwr Csupporting
confidence: 89%
See 4 more Smart Citations
“…Fiber (F) level varied from 14 to 15 % (Table 3), which was in agreement with previous studies using the cultivar BRS 506 (Santos, 2007;Borges et al, 2010;Durães et al, 2012;May et al, 2012). The highest mean value was observed for the March sowing because it had the lowest PC, S, and Q.…”
Section: Monitoring Of the Soil Water Content According To The Llwr Csupporting
confidence: 89%
“…The lowest value was found for the March sowing, which displayed decreased sucrose in the stalk and consequently in the juice. The juice purity (Q) for all the sowing times was higher than 80 % (Table 3), the minimum value according to Durães et al (2012), and higher than the values reported by May et al (2012) (55 %).…”
Section: Monitoring Of the Soil Water Content According To The Llwr Cmentioning
confidence: 54%
See 3 more Smart Citations